Hybrid method for automating generation of reticulated structures (lattice structures) in complex conception domains - Zineb Biallaten; Raddouane Chiheb; Abdellatif El Afia (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A reticulated structure is an interconnexion of bars used to create industrial products. They are rigid and lighter than traditional structures. So they can be the best choice when material gain is an optimization purpose. Generating a reticulated structure automatically is a feature helping industrial players in the design phase. This generation depends on the kind of the conception domain. In this paper we propose a solution that generates a reticulated structure in an arbitrary domain with zero or several holes. The proposed solution is a hybrid method using a technique generating a reticulated structure in a convex conception domain and suggesting a criterion to validate generated segments. Our new algorithm uses a method of computational geometry. We also present a study of the behaviour of a reticulated structure generated using our tool by calculating the deformation energy of this structure.